1999
DOI: 10.1074/jbc.274.11.7361
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Two Phylloquinones, QK and QK′, in an Improved Electron Density Map of Photosystem I at 4-Å Resolution

Abstract: An improved electron density map of photosystem I from Synechococcus elongatus calculated at 4-Å resolution for the first time reveals a second phylloquinone molecule and thereby completes the set of cofactors constituting the electron transfer system of this iron-sulfur type photosynthetic reaction center: six chlorophyll a, two phylloquinones, and three Fe 4 S 4 clusters. The location of the newly identified phylloquinone pair, the individual plane orientations of these molecules, and the resulting distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 36 publications
(44 reference statements)
9
61
0
Order By: Relevance
“…Recent transient Qband EPR of P700 ϩ A 1 Ϫ in PS I single crystals 2 specify an angle of 65 Ϯ 20°between the quinone plane and the plane made up of the crystalline c axis (membrane normal) and the quinone carbonyl bond direction. This is in good agreement with the most recent x-ray structure (10,11). Although the x-ray structure is not sufficiently resolved to identify the amino acids in the binding pocket, electron spin echo envelope modulation studies (12) and a model based on all available structural data (8) suggest that a tryptophan residue may be close to the semiquinone radical in PS I (12).…”
Section: ؊ (253 ؎ 03 å) Is the Same As Between P700supporting
confidence: 72%
“…Recent transient Qband EPR of P700 ϩ A 1 Ϫ in PS I single crystals 2 specify an angle of 65 Ϯ 20°between the quinone plane and the plane made up of the crystalline c axis (membrane normal) and the quinone carbonyl bond direction. This is in good agreement with the most recent x-ray structure (10,11). Although the x-ray structure is not sufficiently resolved to identify the amino acids in the binding pocket, electron spin echo envelope modulation studies (12) and a model based on all available structural data (8) suggest that a tryptophan residue may be close to the semiquinone radical in PS I (12).…”
Section: ؊ (253 ؎ 03 å) Is the Same As Between P700supporting
confidence: 72%
“…The structural data on PS I suggested that the most likely region for binding the phylloquinones was the stretch of highly conserved residues in PsaA and PsaB forming the stromal ␣-helices n and nЈ (2). Additionally, magnetic resonance data indicated that an aromatic nitrogen-containing amino acid was close to the phylloquinone A 1 Ϫ radical (23).…”
Section: Resultsmentioning
confidence: 99%
“…The mutations in PsaA and PsaB were designed by using the crystal structures of PS I and the related purple bacterial reaction center as a guide (2,6,22). The structural data on PS I suggested that the most likely region for binding the phylloquinones was the stretch of highly conserved residues in PsaA and PsaB forming the stromal ␣-helices n and nЈ (2).…”
Section: Resultsmentioning
confidence: 99%
“…ENDOR spectroscopy of the photo-accumulated A 1 Ϫ radical detected an altered electron spin density distribution compared with phyllosemiquinone in vitro (17,18), and it has been suggested that the quinone oxygen(s) are hydrogen-bonded (17), although strong H-bonding would be difficult to reconcile with A 1 's low redox potential and the ability of different quinone compounds to insert into the A 1 site in alternate orientations (21). EPR analysis of photo-accumulated A 1 Ϫ in oriented PS1 (15) and of the P 700 ϩ A 1 Ϫ radical pair in PS1 crystals allowed prediction of the phylloquinone site in the three-dimensional structure (22), and electron densities in this region and the symmetry-related region have been assigned to the two phylloquinones (23). These sites are in an area where the 10th transmembrane ␣-helices of PsaA and PsaB are linked to an ␣-helix parallel to the membrane plane (Fig.…”
Section: Photosystem I (Ps1)mentioning
confidence: 99%